Intervention, Just War, and U.S. National Security - Himes, Kenneth R. 1950- (2004)
[Both the Bush administration's national security strategy and the war with Iraq have provoked wide-ranging reaction and comment. Questions of how to assess the Bush doctrine and/or the Iraqi conflict provoke a reconsideration of the just war tradition. New grounds for just cause are being proposed as well as developments in other areas of just war thinking, including proposals for an entirely new set of criteria, a jus post bellum.]